Males of Ichthyofilaria argentinensis Incorvaia, 1999 and I. bergensis (Wülker, 1930) (Dracunculoidea:Guyanemidae): new morphological aspects and emendation of the generic diagnosis - Cantatore, Delfina M P; Merella, Paolo; Timi, Juan T (Folia parasitologica, 2010)
Abstract: The adult male of dracunculoid nematode Ichthyofilaria argentinensis Incorvaia, 1999 (Guyanemidae) is described for the first time based on specimens found in the swimbladder of its type host, Merluccius hubbsi Marini (Merlucciidae), caught off the coast of Buenos Aires, Argentina (western Atlantic Ocean). In addition, the males of Ichthyofilaria bergensis (Wülker, 1930) Køie, 1993 are redescribed from specimens collected from the body cavity and visceral surface of Molva macrophthalma (Rafinesque) (Lotidae) caught in the western Mediterranean Sea, off the coast of Sardinia. Light and scanning electron microscopy examinations revealed some new morphological features for the genus, such as a pair of deirids located near the end of muscular oesophagus, the body wall conspicuously twisted immediately anterior to the cloaca, the presence of a copulatory plate, one pair of adcloacal papillae and a pair of phasmids situated on the posterior half of the tail. On the basis of this material, the generic diagnosis of Ichthyofilaria is modified to include some of these newly observed features, as well as to indicate the absence of spicules. The diagnosis of Guyanemidae is extended to include that a copulatory plate and/or two spicules may be present as characteristics for this family.
Keywords: Animals; mužské pohlaví; zvířata; Male; Dracunculoidea